Identification of a novel hsa_circ_0058058/miR-324-5p axis and prognostic/predictive molecules for acute myeloid leukemia outcome by bioinformatics-based analysis - Misir, Sema; Ozer Yaman, Serap; Petrović, Nina; Šami, Ahmad; Akidan, Osman; Hepokur, Ceylan; Aliyazicioglu, Yuksel (Biology, 2024)
Acute myeloid leukemia (LAML) is one of the most prevalent hematological malignancies. In recent years, while targeted approaches have shown promise in the fight against cancer, the treatability and prognosis of patients remain inadequate due to the shortage of drugs. Noncoding RNAs, especially circular RNA (circRNA) and microRNA (miRNA), have been shown to play a unique role in tumor development. This study aims to identify the disease-associated circRNA-miRNA-mRNA network by bioinformatic analysis and investigate the mechanisms in the development and progression of LAML. Additionally, it reveals the promising roles of these molecules as a diagnostic biomarker and therapeutic target for LAML treatment. Using various bioinformatics approaches, we identified the hsa_circ_0058058/miR-324-5p axis in LAML and its possible functions in LAML development. According to our results, hsa circ-0058058 can regulate the expression of AP1G1 and SP1 through miR-324-5p to support angiogenesis, the cell cycle, and DNA replication processes. Downregulation of hsa circ-0058058 may contribute to the anticancer functions of miR-324-5p on LAML tumorigenesis, and upregulation of miR-324-5p can abolish the oncogenic effects of AP1G1 and SP1 on LAML tumorigenesis. Additionally, highly enriched pathways indicated possible interactions between molecules underlying LAML pathology. Targeted molecules within this network may be able to function as therapeutic and diagnostic biomarkers for disease, while more research and clinical confirmation are needed.
Gesehen am 24.02.2024